Perceptions of Older Rural Women Using Computerized Programs for Weight Management - Tara Renee O'Brien; Carolyn Jenkins; Elaine Amella; Martina Mueller; Michael Moore; Meredith Troutman- Jordan; Steffanie Sullivan (Rural Nurse Organization; Binghamton University, 2014)
Purpose: To explore older rural women's perceptions of an Internet assisted weight loss program. Sample: The sample (n = 24) included white women (70%) and black women (30%) age 55 and older recruited from two rural senior centers in the Appalachian region of North Carolina. Method: A qualitative design was used to explore rural older obese women's perceptions of an Internet assisted weight loss program using semi-structured interviews.  A total of six focus groups were held with a convenience sample (n=24) of Appalachian adult women (age 55 and older) from two community sites. Findings: The 24 women gave their perspective on the use of the Internet for weight loss.  Six themes emerged from the two groups were: awareness, use of the Internet, personal relationships, self-image, peer support, and obstacles   Conclusions: Weight loss is a sensitive subject matter for rural obese older women.  Evidence from this study suggests that rural women lack social support for weight loss.  Nurses may assist women living in rural areas with weight loss through the use of the Internet weight loss social support program in which older obese women can access in the privacy of their own homes. Keywords: Rural, Technology, Appalachian Region, and Older Adults  DOI:  http://dx.doi.org/10.14574/ojrnhc.v14i2.324